PATHOMORPHOLOGICAL ANALYSIS OF ERBIUM LASER APPLICATION TO CORRECTION OF STRESS URINARY INCONTINENCE IN WOMEN - G. A. Lapiy; A. Y. Yakovleva; N. A. Abdullaev; A. I. Neymark (Сибирский научный медицинский журнал, 2019)
The aim of the investigation is to study the pathomorphological changes in the anterior vaginal wall in women with stress urinary incontinence, who received correction using an erbium laser Fotona. Material and methods. The complex pathomorphological analysis of the biopsy specimens of the vaginal mucosa (VM) in women with stress urinary incontinence (SUI) before and after exposure Er-YAG-laser was performed. Results. It is shown that the main signs of remodeling of VM during SUI are disorganization of fibrillar structures (collagen and elastic fibers) of the intercellular matrix, microcirculation disorders, dystrophic and atrophic changes in the epithelium. After application of laser technology IncontiLase in the VM, signs of stimulation of neocollagenogenesis and neoelastogenesis processes, enhancement of neoangiogenesis, replenishment of a population of synthetically active fibroblasts, increased proliferation (an increase in the index of Ki-67-positive epitheliocytes by 67 %) and improvement of the structure of the vaginal epithelium are revealed. Conclusion. The use of an Er-YAG laser in the correction of SUI in women potentiates the restoration of the morphofunctional organization of VM.